Challenges Faced by Pesantren in South Tapanuli in Implementing the Regulation of the Minister of Religious Affairs No. 31 of 2020 - Mira Rahmayanti Sormin; Adek Kholijah Siregar; Bambang Hermanto Nasution (Perkumpulan Dosen Tarbiyah Islam Indonesia, 2025)
This study aims to analyze the challenges faced by madrasah principals in implementing the Regulation of the Minister of Religious Affairs (PMA) Number 31 of 2020 concerning the Administration of Islamic Boarding School Education in South Tapanuli Regency. The study employed a qualitative, descriptive design. Data were collected through observation, interviews, and documentation involving madrasah principals in Islamic boarding schools. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The findings show that the implementation of PMA Number 31 of 2020 has not been fully optimized because the pesantren and madrasah systems remain integrated. Madrasah principals face administrative, socio-cultural, and resource-related challenges. Administrative challenges include heavy workloads and the transformation of the curriculum from the salaf system to Formal Diniyah Education (PDF) or muadalah. Socio-cultural challenges arise from resistance among senior teachers toward a more formal and structured educational system. Meanwhile, resource limitations are reflected in inadequate facilities and infrastructure, as well as in educators' limited qualifications according to PMA standards. Strategies to address these challenges include administrative digitalization, teacher training, and participatory approaches involving all pesantren stakeholders. The implementation of this PMA requires synergy among madrasah principals, pesantren institutions, the Ministry of Religious Affairs, and local governments to improve the quality of pesantren education while preserving its traditions.